Hiding in Plain Sight: Formation and Function of Stress Granules During Microbial Infection of Mammalian Cells - Tweedie, Alistair; Nissan, Tracy (Frontiers in Molecular Biosciences, 2021)
Stress granule (SG) formation is a host cell response to stress induced translational repression. SGs assemble with RNA binding proteins and translationally silent mRNA. SGs have been demonstrated to be both inhibitory to viruses, as well as being subverted for viral roles. In contrast, the function of SGs during non-viral microbial infections remain a largely unexplored territory. A handful of microbial infections have been shown to result in host SG assembly. Nevertheless, a large body of evidence suggests SG formation in hosts is a widespread response to microbial infection. Diverse stresses caused by microbes and their products can activate the integrated stress response in order to inhibit translation initiation through phosphorylation of the eukaryotic translation initiation factor 2α (eIF2α). This translational response in other contexts results in SG assembly, suggesting that SG assembly can be a general phenomenon during microbial infection. This review explores evidence for host SG formation in response to bacterial, fungal and protozoan infection and potential functions of SGs in the host and for adaptations of the pathogen.